The Potential Role for Securitizing Public Sector Revenue Flows : An Application to the Philippines - Chalk, Nigel (IMF Working Papers; Working Paper ;, 2002)
Since the mid-1980s, the securitization of future flow receivables has grown in importance as a financing alternative for the public sector. In a world of perfect capital markets, there appears to be little rationale-in terms of reducing the average cost of public sector financing-to resort to secured borrowing. However, for many developing countries, financial markets are far from perfect. In particular, there may be an important role for secured financing where increased uncertainty or financial market volatility leads to credit rationing driven by information asymmetries. Secured financing, however, does not provide a free lunch. Such arrangements subordinate existing and future creditors and, as a result, may raise the cost of future borrowing. In addition, high transaction costs, the thin market in secured instruments, the risk of legal challenges, and reduced budget and debt management flexibility may offset the cost advantage of public sector securitization.